The coupled nonlinear Schrodinger-type equations - Abdelrahman, Mahmoud A. E.; Hassan, S. Z.; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2020)
Nonlinear Schrodinger equations can model nonlinear waves in plasma physics, optics, fluid and atmospheric theory of profound water waves and so on. In this work, the exp(-phi(xi))-expansion, the sine-cosine and Riccati-Bernoulli sub-ODE techniques have been utilized to establish solitons, periodic waves and several types of solutions for the coupled nonlinear Schrodinger equations. These methods with the help of symbolic computations via Mathematica 10 are robust and adequate to solve partial differential nonlinear equations in mathematical physics. Finally, 3D figures for some selected solutions have been depicted.
Keywords: Coupled nonlinear Schrodinger-type equations; solitons; exp(-phi(xi))-expansion technique; sine-cosine technique; Riccati-Bernoulli sub-ODE technique; exact solution